2022
DOI: 10.3389/fmats.2021.803106
|View full text |Cite
|
Sign up to set email alerts
|

Property Evaluation of Cement-Stabilized Macadam Modified via Phosphorus Slag Materials

Abstract: Phosphorus slag, known as the waste product of the phosphate ore industry, is causing critical environmental issues due to its direct exposure to natural spaces. In this article, a partial replacement of the natural fine aggregate ordinarily used in cement-stabilized macadam (CSM) base by phosphorus slag was explored to be an effective solution for phosphorus slag waste. CSM specimens were fabricated by adding various dosages of phosphorus slag particle and fine powder, whereas the optimum moisture content and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The initial use of exterior insulation systems in Europe was to compensate for the cracks existing in the wall, while it was later found that exterior insulation systems not only solved the wall cracks problem, but also reduced the building energy consumption and improved the building insulation performance, which is because the composite wall has good insulation performance and heat insulation performance [5]. Serres in France studied a new wall material, COB block, with low LCC, and showed that traditional materials can be used on modern buildings by studying the thermal properties of COB blocks compared with ordinary concrete insulated block walls [8]. At present, the research on new wall materials, especially self-insulation blocks, is increasing in China.…”
Section: Current Research Status Of Self-insulation Wallmentioning
confidence: 99%
“…The initial use of exterior insulation systems in Europe was to compensate for the cracks existing in the wall, while it was later found that exterior insulation systems not only solved the wall cracks problem, but also reduced the building energy consumption and improved the building insulation performance, which is because the composite wall has good insulation performance and heat insulation performance [5]. Serres in France studied a new wall material, COB block, with low LCC, and showed that traditional materials can be used on modern buildings by studying the thermal properties of COB blocks compared with ordinary concrete insulated block walls [8]. At present, the research on new wall materials, especially self-insulation blocks, is increasing in China.…”
Section: Current Research Status Of Self-insulation Wallmentioning
confidence: 99%